FDI Implications of Recent European Court of Justice Decisions on Corporation Tax Matters - BARRY, FRANK (My University, 2010)
Corporation tax rates significantly influence the location of foreign direct investment (FDI) as well as company decisions on corporate borrowing, transfer pricing, dividend and royalty payments, and research and development. While direct taxation remains within the competence of individual EU Member States, the European Court of Justice (ECJ) has faced an increasing number of corporation tax-related cases over recent years and its judgments have significantly redrawn the European tax landscape. The present paper reviews and synthesises these ECJ decisions and analyses their implications for the FDI decisions of multinational corporations.
PUBLISHED
Keywords: Law; foreign direct investment; European Court of Justice; corporation tax